Ali bin Issa Al-Rubaie and his grammatical views (Journal of the College of Basic Education, 2022)
In this research, we stand on a scholar of Arabic scholars, Jalil al-Qadr, a virtuous writer, and a skilled grammarian, whose reputation became famous, and his place rose above his peers in fame and knowledge.